Dampak Penerapan Budaya Tri Hita Karana terhadap Orientasi Kewirausahaan dan Orientasi Pasar serta Konsekuensinya pada Kinerja Usaha (Studi pada Industri Kecil Menengah Kerajinan Perak di Bali) - I Gede Riana; Djumilah Zain; Eka Afnan Troena; Made Sudarma (Jurnal Aplikasi Manajemen, 2012)
This study is intended to know the impact of the implementation of Tri Hita Karana culture toward entrepreneurial orientation, market orientation, and business performance of SMEs of silver craft in Bali. The population of this research is all small and medium size enterprises of silver craft in Bali. By using purposive random sampling, 110 small and medium size enterprises located in four regencies in Bali were selected as samples. The data collection technique was distributing questionnaires. Furthermore, to test the inter-variables influence, inferential analysis of Structural Equation Modeling (SEM) is applied using Partial Least Square (PLS) approach.The finding of this research has given contribution in enlarging the organization culture concept by using local culture values as an organization culture practice. The implementation of Tri Hita Karana culture could improve the entrepreneurial orientation, market orientation, and business performance. It was also found out that the cultural values of Tri Hita Karana are influence the market orientation mediated by entrepreneurial orientation. Moreover, this research reveals the influence of entrepreneurial orientation on market orientation and business performance.Keywords: organization culture of Tri Hita Karana (THK), entrepreneurial orientation, market orientation, and business performance.